Pricing methods in outcome-based contracting: δ2: willingness-to-pay-based pricing. (1st November 2020) - Alkhatib, Nimer S.; Ramos, Kenneth; Erstad, Brian; Slack, Marion; McBride, Ali; Bhattacharjee, Sandipan; Abraham, Ivo
Abstract: Aims: Six Delta is a six-dimensional independent platform for outcome-based pricing/contracting. The second dimension (δ2) estimates prices on the basis of four willingness-to-pay (WTP) thresholds. We describe this dimension's methodology and present a proof-of-concept application to the treatment of non-small cell lung cancer (NSCLC) with EGFR mutation with osimertinib. Materials and methods: Eight WTP scenarios based on four levels of real gross domestic product per capita (<1GDP/capita, 1 × GDP/capita, 3 × GDP/capita, and >3 × GDP/capita) and two market conditions (monopolistic versus competitive) were assumed. The incremental cost-utility ratio (ICUR) was applied to differently to both markets. In the monopolistic market, assuming no competitors, the cost/QALY ratio for a drug was used; whereas in the competitive market, assuming competitors, the incremental cost-utility ratio (ICUR) was applied. One-way sensitivity analyses were performed and predictive equations were specified to estimate the prices of treatment for the resulting eight WTP scenarios; for which subsequently the average and standard deviation were calculated. A gamma distribution was specified and Monte Carlo Simulation (MCS) was applied to estimate the dimension-specific price based on WTP (DSPWTP ). A proof-of-concept exercise with osimertinib in NSCLC was performed for two hypothetical outcome-based contracts: 1-year (2019–2020) and 2-year (2019–2021). The 2018 wholesale acquisition cost (WAC) of 14, 616 (30-day prescription) was used to estimate the DSPWTP for each contract. Results: The 1-year estimates averaged 4, 654 (SD=6, 462) and the MCS yielded a DSPWTP of 4, 547 or −68.89% of the 2018 WAC for a 30-day prescription. The 2-year estimates averaged 4, 7667 (SD=6, 480) with the MCS generating a DSPWTP of 4, 704 or −67.82% of the WAC. Conclusions: We demonstrated that WTP-based methods that include various WTP thresholds and market conditions generate price estimates across these thresholds and market conditions that can be integrated into our proposed Six Delta platform for outcome-based pricing/contracting.